PERAN PONDOK PESANTREN DALAM MENANGGULANGI KENAKALAN REMAJA - Azhari Azhari (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2019)
Pondok Pesantren is a rich cultural treasures of typical Indonesian Muslims. From the results Obsevasi author in Pondok Pesantren Darul Ikhlas whose presence is expected to answer the challenge-the hand of modernity in society. So this research author gave the title: The role of Pondok Pesantren in Tackling Youth Delinquency (Case Study Pondok Pesantren Darul Ikhlas Pagar Alam City). This study aims 1) Analyzing the shape of mischief Santri in Pondok Pesantren Darul Ikhlas Pagar Alam City. 2) Analyzing Supporting Factors and barriers in overcoming the mischief of students at Pondok Pesantren Darul Ikhlas Pagar Alam City. 3) Analyzing the Rare Pondok Pesantren Darul Ikhlas Pagar Alam City in mencega and overcome juvenile delinquency (santri) Pondok Pesantren Darul Ikhlas Pagar Alam City.The type of research that the authors use in this study is Field Research. with qualitative methods. The data collection technique is done by using observation method, interview method, documentation method. The subject of this research is the Leader of Pondok Pesantren, Vice Chairman of Pondok Pesantren, Boarding House Dormitory, Teachers of Pesantren Darul Ikhlas Kota Pagara Alam and the committee (wali santri). From the results of this study can be known The forms of mischief students of Pondok Pesantren Darul Ikhlas is ditching school, dressing inappropriate, less attitude to the teacher, coming late, smoking, making a fuss in the classroom at the time of study, not follow KBM. The causes of delinquency students of Darul Ikhlas Islamic Boarding School is the influence of the family is less harmonious, for fun, looking for attention, influence friends / environment, association, atmosphere in the Dormitory less attention. The effort of Pondok Pesantren Darul Ikhlas in responding to juvenile delinquency is to conduct Preventive Action, Repressive Action: Conducting curative action Directing to students to use their spare time with positive actions by following extracurricular provided by Pondok Pesantren.